"Eu era oficialmente uma artista louca": uma análise da autobiografia em quadrinhos de Ellen Forney - Santos, Diego Luiz dos (2017)
This dissertation problematizes the graphic memoir named Parafusos: Mania, Depressão, Michelangelo e Eu, written and drawn by the american cartoonist Ellen Forney, which translated the original Marble: Mania, Deprresion, Michelangelo and Me (2012) was published in Brazil in 2014. The book tells the experiences Ellen in search of medication, therapy or a way of life that would make her feel good herself even after being diagnosed bipolar, shortly before her thirtieth birthday. During her research, which lasted four years (1998-2002), the cartoonist found inspiration assumed voluntarily the sobriquet of “crazy artist” in reference to known artists that were diagnosed with some mental disorder, like Van Gogh and Sylvia Plath. Starting from this premise, the work consists in valorize what Ellen tells about her life and about her madness, why tells it and how tells it. Therefore, the investigations inserts in a trend of the studies field known as history of madness and psychiatry which, since the decade of 1990, have gained visibility while inserting and valorizing the point of view, of the so called “crazy” in historiography. The main objective of the dissertation was problematizing the book Parafusos, in the sense of: showing how Ellen explain, describes and reflects about herself starting from the moment that she diagnosed with bipolar disorder; how comprehends this disorder and deals with the diagnosis and, in the light of this, diagnosed with the “psychiatry science”, appropriating or not of the referring of this field (concepts, treatment, etc.) but also searching other non-scientific ways such as treatment and alternative therapy; besided understanding how and what way the author builds and reinvented herself starting from the diagnosis inspiring in known artists from the past and constituting herself as “crazy artist”.